The Role of Government Spending in Water Pollution Control - Ari Anggrayni Ramadhan; Benedictus Raksaka Mahi (Economics Development Analysis Journal, 2025)
The global clean water crisis is an urgent challenge. Althought the water stress level in most provinces in Indonesia remains low, the water quality index does not reach good status. Water quality index calculated through pollution index of surface water. This study examines how environmental protection spending by local governments defined as the combined spending of provincial and regency/municipality governments within each province affects the water quality index in Indonesian provinces, and compare it with central government spending and non-government spending. Government spending has three effects on water pollution: scale, composition, and technique effects. These three effects are expected to follow a quadratic pattern.  Using provincial panel data from 2017 – 2022, this study estimates these with fixed effect model. Initially, the estimation uses quadratic specification on local government spending, but likelihood ratio test shows that the quadratic term does not improve model fit, so the analysis proceeds with the linear specification. The results show that local government spending and non-government spending increase the water quality index, but central government spending is not significant due to its long-term effects. Non-government spending is more effective than government spending. Therefore, the local government should enforce regulations on businesses/ local-owned enterprises that use surface water to make efforts to maintain water sources. In addition, the local government needs to consider the development of a localized wastewater management system but still considering the necessary technical matters.